Charles Edward of Saxe-Coburg : the German Red Cross and the plan to kill "unfit" citizens 1933-1945 - Rushton, Alan R. (Cambridge Scholars Publishing, 2018)
Charles Edward was ruler of the German Duchy of Saxe-Coburg and Gotha, president of the German Red Cross, and the grandson of Queen Victoria. He was closely allied with the rise of Adolf Hitler and the implementation of eugenic policies designed to improve German racial health. When war began in 1939, Hitler ordered a secret program of murder by poison gas and starvation to eliminate the mentally and physically handicapped ""ballast people""; approximately 250,000 people were eventually killed. Readers in medicine, law, sociology and history will be interested in this tragic story of a weak-wi